1994
DOI: 10.1177/026835559400900304
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Varicose Vein Recurrence by Use of Postoperative Compression Stockings

Abstract: Objectives: To assess the ability of compression stockings to reduce the postoperative recurrence of varicose veins after surgery and to assess patient compliance. Design: Prospective randomized trial with follow-up to 1 year after surgery. Patients: Sixty-nine patients presenting for varicose vein surgery. Interventions: Interview for stocking compliance postoperatively with clinical and Doppler assessment of recurrence at 3, 6, 9 and 12 months postoperatively. Main outcome measures: Recurrence of varicositie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 6 publications
0
13
0
1
Order By: Relevance
“…6,7 Compression with a class II MCS (23 to 32 mm Hg), worn for 12 months after the surgical procedure, has been shown to be effective in reducing the incidence of recurrent varicose veins. 8 The rationale for elastic compression use varies depending on whether the varicose disease is treated with more traditional surgical stripping or with endovascular or other techniques. In the first two types of treatment, use of concentric compression, with a bandage or MCS, is very widespread, at least for the first 24 to 48 hours.…”
mentioning
confidence: 99%
“…6,7 Compression with a class II MCS (23 to 32 mm Hg), worn for 12 months after the surgical procedure, has been shown to be effective in reducing the incidence of recurrent varicose veins. 8 The rationale for elastic compression use varies depending on whether the varicose disease is treated with more traditional surgical stripping or with endovascular or other techniques. In the first two types of treatment, use of concentric compression, with a bandage or MCS, is very widespread, at least for the first 24 to 48 hours.…”
mentioning
confidence: 99%
“…Many authors have shown the effectiveness of compression in preventing or minimizing inflammation and pain, bruising, hematoma and hemorrhage, thrombosis of superficial and deep vein, and even in preventing recanalization and neovascularization; finally, compression therapy seems to shorten recovery time and sick leave. 4,5,[23][24][25][26][27][28][29][30][31][32] Nevertheless, despite of many reported beneficial effects on post-procedure symptoms and signs, compression therapy after VV treatment is still debated and not generally applied. In some papers, no advantages from compression over no compression were reported.…”
Section: Discussionmentioning
confidence: 99%
“…eine Progredienz der Varikose sollen durch die Anwendung von Kompression reduziert werden (10,30). DarĂŒber hinaus fĂŒhrt die Kompression zu einer Verringerung der postoperativen Schmerzen und des postoperativen Ödems (6,16,17,27,28).…”
Section: Discussionunclassified